Le commentaire œnologique ou comment déguster le vin par les mots - Audrey Moutat (Lexis: Journal in English Lexicology)
This paper is part of a wider study on the discourse on perception I have conducted in the past few years. I had two goals: (i) on the one hand, I tried to determine how people use the French language in order to talk about their perceptions; (ii) on the other hand, I wanted to understand how the perceived phenomena thus described are organized into morphological forms and become significant. To carry out this study, I decided to work on wine tasting to identify, describe and evaluate how the organoleptic qualities of a wine are perceived. I built a corpus comprising tasting notes published in five French “oenological” magazines sold in newsstands. I aimed to identify communication devices used by professional tasters to describe the complexity of the wines tasted. I particularly focused on the lexicon of taste and thus evaluated the relevance of this terminology by studying the interpretive pathways it induces. Both the interpretive semantics developed by François Rastier and Jean-François Bordron’s theory of iconicity allowed me to find the common organization between perception (the organoleptic qualities of a wine) and language (the semantic properties of the wine terminology). Indeed, I noticed that this wine terminology, sometimes considered “metaphorical”, is similar to the terminology relating to perceptions deriving from different senses.